Left Lower Lung Collapse in a Patient Undergoing Endoscopic Procedure - Akshatha Kamath; Joel Yarmush; Sneha Rao (Case Reports in Anesthesiology)
ASA closed claims from 2000 to 2009 have shown that adverse respiratory events are more common in nonoperating room locations like endoscopy suite than in the operating room (44% v/s 20%). Here, we report a case of lung atelectasis which resulted in hypoxemia in a malnourished patient undergoing endoscopic procedure. It is crucial to identify the high-risk patients and monitor them appropriately in the postoperative phase. Continuous capnometry may offer additional benefit by identifying hypercapnia, hypoventilation at the earliest in the recovery area, thus preventing serious complications.